Design and preparation of superwetting polymer surface. (9th January 2020) - Wang, Songhe; Zhang, Xiaohong; Guo, Zhaoyan; Jiang, Haibin; Qiao, Jinliang
Abstract: A new strategy to prepare superwetting polymer surface is reported in this paper. Polypropylene sheets with superhydrophilic, superlipophilic and superamphilic surfaces can be prepared easily by using this strategy. PP sheet with a superhydrophilic surface or a superlipophilic surface was prepared by grafting hydrophilic monomer or lipophilic monomers onto PP sheet with a microporous surface. The microporous surface of PP sheet displays contact angle of 0° for aqueous and oily liquids when both hydrophilic and lipophilic monomers were grafted onto PP microporous surface, indicating that superamphilic PP surface can be also obtained by using this strategy. The effects of grafting modification on surface morphology and chemical composition were investigated and the mechanism of superwetting was explored. It is well known that PP cannot be bonded by aqueous binder, while PP with superhydrophilic surface prepared in this work can be bonded together by aqueous binder with bonding strength of 8Kpa. Graphical abstract: Image 1 Highlights: Superwetting Polymer Surfaces were designed. Superhydrophilic surface was prepared by grafting sodium maleate onto the PP sheet with micropores. Superlipophilic surface was prepared by grafting unsaturated silicon oil onto the PP sheet with micropores. Superamphilic surface was prepared by grafting sodium maleate and unsaturated silicon oil onto the PP sheet with micropores. Superhydrophilic and superamphilic surfaces can be bonded together by aqueous binder.